Is Job Insecurity Harmful to All Types of Proactivity? The Moderating Role of Future Work Self Salience and Socioeconomic Status - He, Kaiyuan; Wang, Jigan; Sun, Muyun (Frontiers in Psychology, 2022)
How and when do uncertain factors affect employees’ different types of proactive behavior? Building on the strength model of self-control, the present study examines the different effects of job insecurity on individual-oriented and organizational-oriented proactive behavior, and the moderating role of future work self salience (FWSS) and socioeconomic status (SES). A two-wave data collected from 227 employees in China was used to test our hypotheses. The results indicate that job insecurity is negatively associated with all the proactive behavior. Moreover, FWSS positively moderates the relationship above, and the moderating role on individual-oriented proactive behavior is stronger than organizational-oriented proactive behavior. SES negatively moderates the relationship between job insecurity and the two types of proactive behavior. In addition, FWSS and SES have a three-way interactive effect on the relationship between job insecurity and individual task proactive behavior. The practical implications of these results are discussed.